EFFECT OF DIFFERENT FEEDING RATES OF CORN COB FLOUR SUPPLEMENTED-FEED ON THE GROWTH OF FARMED Osphronemus gouramy - Yulfiperius, Yulfiperius; Firman, Firman; Hartini, Sri (Politeknik Kelautan dan Perikanan Jembrana, 2024)
The rapid growth of the aquaculture industry and the limited availability of conventional fish feed have driven the need for alternative feed sources, particularly in intensive fish farming systems. This study, conducted from May 15 to July 5, 2017, in Bengkulu, aimed to determine the optimal feeding rate for gourami (Osphronemus goramy) using artificial fish pellets. A completely randomized design was applied, testing four feeding rates based on fish biomass: D1 (2%), D2 (3%), D3 (4%), and D4 (5%) per day. Gouramis (3.2–3.3 g, 1.1–1.3 cm) were reared in 24 plastic containers (50×30×27 cm3) under controlled water quality conditions. The results showed that a 5% feeding rate (D4) yielded the best outcomes in absolute length (1.97 ± 0.13 cm), specific growth rate (2.78 ± 0.17% day⁻¹), feed conversion ratio (3.72 ± 0.11), feed efficiency (26.85 ± 0.30%), and survival rate (88.89%). Statistical analysis revealed that different feeding rates significantly influenced absolute length, specific growth rate, and feed conversion ratio, while feed efficiency and survival rate remained unaffected. Despite the promising growth performance at higher feeding rates, the high feed conversion ratio and low feed efficiency highlight the need for improved feed formulations. Future research should focus on optimizing corn cobs as a complementary ingredient to enhance feed efficiency, minimize waste, and contribute to sustainable aquaculture. Incorporating corn cob-based feeds could improve waste management and provide economic benefits to fish farmers.Pesatnya pertumbuhan industri akuakultur dan keterbatasan ketersediaan pakan ikan konvensional mendorong perlunya sumber pakan alternatif, terutama dalam sistem budidaya ikan intensif. Penelitian ini, yang dilaksanakan pada tanggal 15 Mei hingga 5 Juli 2017 di Bengkulu, bertujuan untuk menentukan tingkat pemberian pakan optimal bagi ikan gurami (Osphronemus gouramy) menggunakan pakan buatan ikan. Rancangan acak lengkap diterapkan dengan menguji empat tingkat pemberian pakan berdasarkan biomassa ikan: D1 (2%), D2 (3%), D3 (4%), dan D4 (5%) per hari. Ikan gurami (3,2–3,3 g, 1,1–1,3 cm) dipelihara dalam 24 wadah plastik (50×30×27 cm³) dengan kualitas air yang terkontrol. Hasil penelitian menunjukkan bahwa tingkat pemberian pakan 5% (D4) memberikan hasil terbaik dalam hal panjang mutlak (1,97 ± 0,13 cm), laju pertumbuhan spesifik (2,78 ± 0,17% hari⁻¹), rasio konversi pakan (3,72 ± 0,11), efisiensi pakan (26,85 ± 0,30%), dan tingkat kelangsungan hidup (88,89%). Analisis statistik menunjukkan bahwa tingkat pemberian pakan yang berbeda berpengaruh signifikan terhadap panjang mutlak, laju pertumbuhan spesifik, dan rasio konversi pakan, sedangkan efisiensi pakan dan tingkat kelangsungan hidup tidak terpengaruh. Meskipun tingkat pemberian pakan yang lebih tinggi menghasilkan pertumbuhan yang lebih baik, tingginya rasio konversi pakan dan rendahnya efisiensi pakan menunjukkan perlunya perbaikan formulasi pakan. Penelitian lebih lanjut perlu difokuskan pada optimalisasi tongkol jagung sebagai bahan tambahan pakan untuk meningkatkan efisiensi pakan, mengurangi limbah, dan mendukung kegiatan akuakultur berkelanjutan. Penggunaan pakan berbasis tongkol jagung juga dapat membantu pengelolaan limbah serta memberikan manfaat ekonomi bagi pembudidaya ikan.